STRATEGI ADAPTASI PEDAGANG ANGKRINGAN DALAM MEMPERTAHANKAN EKSISTENSI HIDUP STUDI DI KAWASAN JL. K.H. ALI MAKSUM KRAPYAK YOGYAKARTA (Perbandingan Antara Angkringan Tradisional Versus Angkringan Modern) - Kurniati . (JESI (Jurnal Ekonomi Syariah Indonesia), 2015)
Abstract The theme of this research on adaptation strategies angkringan traders to exist in the face of the dynamics of life in the surrounding area of Jl. K.H. Ali Maksum Krapyak, Bantul, Yogyakarta. Researchers want to know how the strategy or the efforts made by angkringan traders in order to maintain his existence and how social capital, which in turn play a role in these efforts. The strategy can be formulated as an effort to maintain his existence as a angkringan’s trader around Jl. K.H. Ali Maksum Krapyak, Bantul, Yogyakarta. The method used in this research using descriptive qualitative method. In this study, there are two classiﬁ cations of traders who hung (trade) around the area of Jl. K.H. Ali Maksum Krapyak, Bantul, Yogyakarta, which is used as one of the objects of informants, namely traders patterned angkringan traditional and modern. Through the narrative they can know how the efforts and strategies undertaken to maintain his existence in the face of the dynamics of life in the surrounding area of Jl. K.H. Ali Maksum Krapyak, Bantul, Yogyakarta. The strategy is one of them is to increase infrastructure facilities in Angkringan, such as a more representative (wider), Television, snacks are varied, not only the main menu as in angkringan others. In this study found the factors underlying the existence of traders angkringan and efforts are being made to defend themselves in the face of the local economy. Keywords: Existence, Strategy adaptation, Angkringan Traders, Krapyak Bantul.